Assignment of machines in cell layout using modified artificial bee colony algorithm. (2017) - Adinarayanan, A.; Uthayakumar, M.; Prabhakaran, G.; Anbumalar, V.
Cellular manufacturing (CM) is now an established international practice to integrate: equipment, people, and systems into 'focused factories', 'mini-businesses' or 'cells' with clear customers, responsibilities and boundaries. The major element in exploiting the benefits of CM is efficient layout designs. In this paper, problem of machine assignment is considered in a cellular layout. The focus is on the intra-cell machines allocation, because the inter-cell material flows should be minimal in CM. The modified artificial bee colony (MABC) algorithm is proposed to solve the layout problem. The algorithm tackles one cell at a time with a maximum of nine machines, which will be assigned into a 3 × 3 grid space according to the ranking result. This problem involves five parts and five quantitative demand periods are considered. To examine the performance of the proposed MABC, datasets are taken from the literature and the results are compared with those of other approaches. The proposed MABC provides an optimal layout exactly.